Phonological complexity in school-aged children who stutter and exhibit a language disorder. - Wolk, Lesley; LaSalle, Lisa R (Journal of fluency disorders, 2015)
PURPOSE: The Index of Phonological Complexity and the Word Complexity Measure are two measures of the phonological complexity of a word. Other phonological measures such as phonological neighborhood density have been used to compare stuttered versus fluent words. It appears that in preschoolers who stutter, the length and complexity of the utterance is more influential than the phonetic features of the stuttered word. The present hypothesis was that in school-age children who stutter, stuttered words would be more phonologically complex than fluent words, when the length and complexity of the utterance containing them is comparable. School-age speakers who stutter were hypothesized to differ from those with a concomitant language disorder., METHODS: Sixteen speakers, six females and ten males (M age=12;3; Range=7;7 to 19;5) available from an online database, were divided into eight who had a concomitant language disorder (S+LD) and eight age- and sex-matched speakers who did not (S-Only)., RESULTS: When all stuttered content words were identified, S+LD speakers produced more repetitions, and S-Only speakers produced more inaudible sound prolongations. When stuttered content words were matched to fluent content words and when talker groups were combined, stuttered words were significantly (p<=0.01) higher in both the Index of Phonological Complexity and the Word Complexity Measure and lower in density ("sparser") than fluent words., CONCLUSIONS: Results corroborate those of previous researchers. Future research directions are suggested, such as cross-sectional designs to evaluate developmental patterns of phonological complexity and stuttering plus language disordered connections., EDUCATIONAL OBJECTIVES: The reader will be able to: (a) Define and describe phonological complexity; (b) Define phonological neighborhood density and summarize the literature on the topic; (c) Describe the Index of Phonological Complexity (IPC) for a given word; (d) Describe the Word Complexity Measure (WCM) for a given word; (e) Summarize two findings from the current study and describe how each relates to studies of phonological complexity and fluency disorders. Copyright © 2014 Elsevier Inc. All rights reserved.
12 citations (Crossref) [2023-10-31] Place: United States Wolk, Lesley. Southern Connecticut State University, Department of Communication Sciences and Disorders, 501 Crescent St, New Haven, CT 06515, United States. Electronic address: Lesleywolk@sbcglobal.net. LaSalle, Lisa R. Communicative Disorders, University of Redlands, 1200 E Colton Ave., Redlands, CA 92373, United States.
Keywords: *Language; *Linguistics; *Phonetics; *Stuttering; Adolescent; Adult; Article; Child; Concomitant disorders; Female; Humans; Language; Language disorders; Linguistics; Male; Phonetics; Phonological complexity; Schools; Speech; Speech Production Measurement; Stuttering; adolescent; adult; child; controlled study; data base; dept.cmd; female; fluency disorder; human; language; language disability; linguistics; male; phoneme; phonetics; school; school child; speech; speech analysis; stuttering